Novel magnetite nanoparticles coated with waste sourced bio-based substances as sustainable and renewable adsorbing materials - Magnacca, Giuliana (2014)
This study examines the possibility of using bio-based product isolated from urban solid wastes as a material for environmental technological applications. To this end, Fe3O4 nanoparticles coated with different amounts of soluble bio-based products (SBO) were synthesized as low-cost nanoadsorbent for the removal of pollutants in wastewater. Particles of 10 nm diameter with Fe3O4 core and SBO shell were obtained. The concentration of SBO employed in the synthesis had no effect on the size and structure of the NPs, but ruled the pHPZC and aggregation of the nanoparticles in water. The cationic dye crystal violet (CV) was used as a model pollutant to test the adsorption capacity of the nanoparticles. The results indicated that both the medium pH and NP dosage were significant parameters to enhance the removal of CV. The results contribute to the studies which show how wastes can become a source of revenue through the industrial exploitation of their chemical value.